Detection of traces of calcium oxalate druses in fossil leaves of angiosperms and gymnosperms from different sites and geological periods - Mahdieh Malekhosseini; Hans-Jürgen Ensikat; Victoria E. McCoy; Torsten Wappler; Jes Rust (PLoS ONE, 2025)
Calcium biomineralization in plants occurs in a variety of patterns such as calcium carbonate cystoliths and calcium oxalate (CaOx) crystals and agglomerates in different forms. CaOx druses and prismatic crystals with sizes between 20–100 µm are found in large amounts in the leaves of many extant plants, in angiosperms particularly in dicotyledons. In gymnosperms, large CaOx druses are often found in Cycadales and Ginkgo along the leaf veins, while most conifers contain microcrystals of <10 µm size in the parenchyma. In plant fossils, patterns of calcium biominerals are rarely reported because they usually disappear during fossilization. Traces of CaOx druses have been reported recently in fossils of dicotyledon plant leaves from Oligocene; here the CaOx was replaced by organic or mineral compounds. But there is still no certain report of CaOx druses traces in Paleozoic or Mesozoic fossils. In the study presented here, granular structures in fossil leaves from different sites across the Devonian to the Neogene were investigated and compared with biomineral patterns in extant leaves of gymnosperm and angiosperm trees. These granular structures resembled patterns of CaOx druses in extant leaves in morphology and distribution and were interpreted as probable casts of CaOx druses. Well-preserved angiosperm fossils from various sites such as seed ferns since Devonian, and Ginkgophytae since Carboniferous all showed such granular traces. The diverse chemical composition of these casts of CaOx druses (e.g., pyrite, iron oxide, organic material, SiO 2 ) depends on fossilization conditions and the chemistry of the surrounding matrix. Good knowledge of the morphology and distribution patterns of biominerals in all relevant plant groups is a basic prerequisite for recognizing their traces in plant fossils. This first extensive study of previously overlooked traces of CaOx druses in plant fossils is a promising step toward a more detailed identification of these fossil microstructures.